ظاهرة تدريس الأصوات العربية - Albarra Sarbaini (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
A language is made up of units of units of a particular sound, with the sound unit up unit formed millions and millions of words in diverse situations. Each language is a bona fide treasures of the selected sound from all possible sounds that can be spoken man, which may differ from other treasures of the sounds of language. Arabic sounds denoted by "ض" for example, is not found in other languages. The substance of the sound is also different between one language to another language, the difference is exactly what became the beginning of the sound teaching problem. Number of Arabic alphabet is not much different from the number of alphabetic languages ​​other languages, but Arabic has a long vowel sounds in addition to the applicable short vowel regularly. So also with the sound madd, syiddah and ghunnah with variations that will eventually give birth to the sound of the sound that gets the emphasis on a word (NaBr) and the tone or tune a particular song on a sentence (tanghim) according to the size of a strong and level geloranya meaning behind the words concerned. Key Words: Language Elements, Sounds of language